Emotional Intelligence and Cognitive Abilities - Purificacion Checa; Pablo Fernandez-Berrocal (Frontiers Media SA, 2016)
Nowadays, not only psychologists are interested in the study of Emotional Intelligence (EI). Teachers, educator, managers, employers, and people, in general, pay attention to EI. For example, teachers would like to know how EI could affect student$1 (Bs academic results, and managers are concerned about how EI influences their employees$1 (Bperformance. The concept of EI has been widely used in recent years to the extent that people start to applying it in daily life. EI is broadly defined as the capacity to process and use emotional information. More specifically, according to Mayer and Salovey, EI is the ability to: (3z(B1) accurate perception, appraise, and expression of emotion; 2) access and/or generation of feelings when they facilitate thought; 3) understand emotions and emotional knowledge; and 4) regulate emotions to promote emotional and intellectual growth(3y (B(Mayer and Salovey 1997, p. 10). When new information arises into one specific area of knowledge, the work of the scientists is to investigate the relation between this new information and other established concepts. In this sense, EI could be considered as a new framework to explain human behaviour. As a young concept in Psychology, EI could be used to elucidate the performance in the activities of everyday life. Over the past two decades, studies of EI have tried to delimitate how EI is linked to other competences. A vast number of studies have reported a relation between EI and a large list of competences such as academic and work success, life satisfaction, attendee to emotions, assertiveness, emotional expression, emotional-based decision making, impulsive control, stress management, among others. Moreover, recent researches have shown that EI plays an important role in the prediction of behaviour besides personality and cognitive factors. However, it is not until quite recently, that studies on EI have considered the importance of individual differences in EI and their interaction with cognitive abilities. The general issue of this Research Topic was to expose the role of individual differences on EI in the development of a large number of competencies that support a more efficient performance in people$1 (Bs everyday life. The present Research Topic provide an extensive review that may give light to the better understanding of how individual differences in EI affect human behaviour. We have considered studies that analyse: 1) how EI contributes to emotional, cognitive and social process beyond the well-known contribution of IQ and personality traits, as well as the brain system that supports the EI; 2) how EI contributes to relationships among emotions and health and well-being, 3) the roles of EI during early development and the evaluation in different populations, 4) how implicit beliefs about emotions and EI influence emotional abilities.s
English
Keywords: emotion; Well-being; Intelligence; Health; Personality; cognitive abilities; creativity; Emotional Intelligence